SOME ALTERNATIVES TO DEVELOPMENTS : LESSONS FOR LIBYA - Bryce , Murray (Dirasat in Economics and Business, 1968)
There was once a mission to an underdeveloped country which da lack of resources and a great deal of poverty. The people in The country said, “What do you recommend we do for economic development ?" The answer was : “You should find oil !” Libya has already followed this advice with such success that even the people in the oil business are almost embarrassed by the wealth that they have found. This creates not only an interesting challenge of how to develop with riches, but also proves that capital is not neccessarily the most important factor in development. Capital alone is not worthless, but it certainly does not solve all of the problems — it merely solves one part of the problem and it even creates some cihers. Fortunately, the problems are the comparatively happy ones of riches. Nevertheless, unless their existence is realized, oil could turn out in the long run not to be a blessing to a country like Libya. Another lesson learned over the years in economic development work is that underdeveloped countries have an enormous diversity .The range of problems is much greater than was once realized. At one time it was thought that the problem was a common one of lack of resources or lack of capital, usually with a surplus of labor.